2020
DOI: 10.1007/s42452-020-03261-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geosynthetic reinforcement on the bearing capacity of strip footing on sandy soil

Abstract: Due to the increasing presence of problematic soils, expansive clays and highly compressive sand engineers are using a verity of soil improvement techniques to treat such soils. While geosynthetics are extensively used for improving soil characteristics in roads, pavements and embankments, it can also be used to increase the lack of bearing capacity of residential housing or lightweight structures constructed on sandy soils. In order to simulate site conditions in the laboratory environment, a laboratory-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…It was found that nonwoven fabric provided additional constraints to the soil and increased the strength of the specimens. Al Subari et al [11] carried out consolidated undrained triaxial tests on sand reinforced with coir and found that the addition of coir reinforcement has increased the shear strength of the reinforced sand. Markou [12] studied the influence of particle shape and size on the mechanical properties of geotextile-reinforced sand and found that the strength of the reinforced specimens with angular grains is higher than that of round grains.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that nonwoven fabric provided additional constraints to the soil and increased the strength of the specimens. Al Subari et al [11] carried out consolidated undrained triaxial tests on sand reinforced with coir and found that the addition of coir reinforcement has increased the shear strength of the reinforced sand. Markou [12] studied the influence of particle shape and size on the mechanical properties of geotextile-reinforced sand and found that the strength of the reinforced specimens with angular grains is higher than that of round grains.…”
Section: Introductionmentioning
confidence: 99%